Sebuah Kajian Mengapa Akuntansi Syariah Masih Sulit Tumbuh Subur di Indonesia - Virginia Nur Rahmanti (Journal of Accounting and Investment, 2012)
Nowadays, shariah model is increasingly favoured by the world society, especially Indonesian. It's proved by Indonesian Bank report year ended 2011 which shows increasing number of shariah financial institution either in the downtown or sub urban area. Nevertheless the sharia'ate development in Indonesia that was born on 1992nd  signed by the established of Bank Muamalat Indonesia, still shows low quality. Factually, human resources is the main factor which determine the success of shari'ate in Indonesia. Indonesian human resource asset seems unready to control shariah scheme, it's proved by the low-level of their understanding in about the human responsibility to the God (habluminallah) and to another people (habluminannas). This condition worsen by their reluctant to learn about shariate holistically. In their mind, shariate just define by kinds of transaction without riba, whereas the thruth shariate concept is wider than just usury. Likely, these fenomena cause the gap between Islamic shariate concept and pratical become wider. In the other side, most practioners try to think out of the box from the prison of shariate financial standard (PSAK syariah), because they think that PSAK syariah isn't truly shari'ah like Islamic shariate determined. This research using interpretive methodology with fenomenology approachment. Informan used including academics, practitioners and standard maker (Dewan Standar Akuntansi Syariah). Data gathering method using literature analysis, interview and observation. Researcher hope from this research will find conclusion about the reason of this slow development of shariate in Indonesia.